Mono- and bithiophene-substituted diarylethene photoswitches with emissive open or closed forms - Schleper, A. Lennart; Bossi, Mariano L.; Belov, Vladimir N.; Hell, Stefan W. (Beilstein Journal of Organic Chemistry, 2019)
We present a new series of photochromic 1,2-bis(2-ethylbenzo[b]thiophen-3-yl)perfluorocyclopentenes with an oxidized benzothiophene core (O) or a nonoxidized one, decorated with mono- (Th1) and bithiophene (Th2) units attached to positions 6 and 6′ (Sy = symmetric) or only to position 6 (As = asymmetric). “Oxidized” compounds have highly fluorescent closed forms emitting in the visible region (yellow to red). The dyes with nonoxidized benzothiophenes possess fluorescent open forms with rather low emission efficiency. The photoswitching kinetics was studied at several wavelengths with UV and visible light. New diarylethenes underwent ring-closure reactions by irradiation with UV light (365 nm, 405 nm), and the reversible ring-opening by irradiation with visible light (470 nm, 530 nm). The on-switching of fluorescence due to the ring-closure reaction was observed also with visible light of 470 nm (to an extent of 10% for compound SyOTh1) and attributed to the Urbach tail effect. Due to a high degree of fluorescence modulation (>270), good fatigue resistance and large fluorescence quantum yield, compound SyOTh1 emerged as a candidate for single-molecule based super-resolution fluorescence microscopy.
Keywords: diarylethenes; dyes; fluorescence; organic synthesis; photochromism; photoswitching

(untitled) - Irie, M.; Fukaminato, T.; Matsuda, K.; Kobatake, S. (Chem. Rev., 2014)

(untitled) - Jeong, Y.-C.; Yang, S. I.; Ahn, K.-H.; Kim, E. (Chem. Commun., 2005)

(untitled) - Jeong, Y.-C.; Yang, S. I.; Kim, E.; Ahn, K.-H. (Tetrahedron, 2006)

(untitled) - Barrez, E.; Laurent, G.; Pavageau, C.; Sliwa, M.; Métivier, R. (Phys. Chem. Chem. Phys., 2018)

(untitled) - Uno, K.; Bossi, M. L.; Konen, T.; Belov, V. N.; Irie, M.; Hell, S. W. (Adv. Opt. Mater., 2019)

(untitled) - Åslund, A.; Herland, A.; Hammarström, P.; Nilsson, K. P. R.; Jonsson, B.-H.; Inganäs, O.; Konradsson, P. (Bioconjugate Chem., 2007)

(untitled) - Becker, R. S.; Seixas de Melo, J.; Maçanita, A. L.; Elisei, F. (J. Phys. Chem., 1996)

(untitled) - Krayushkin, M. M.; Bogacheva, A. M.; Levchenko, K. S.; Kobeleva, O. I.; Valova, T. M.; Barachevskii, V. A.; Pozzo, J.-L.; Struchkova, M. I.; Shmelin, P. S.; Kalik, M. A.; Baryshnikova, T. K.; Charushin, V. N. (Mendeleev Commun., 2013)

(untitled) - Uno, K.; Niikura, H.; Morimoto, M.; Ishibashi, Y.; Miyasaka, H.; Irie, M. (J. Am. Chem. Soc., 2011)

(untitled) - Roubinet, B.; Weber, M.; Shojaei, H.; Bates, M.; Bossi, M. L.; Belov, V. N.; Irie, M.; Hell, S. W. (J. Am. Chem. Soc., 2017)

(untitled) - Chotana, G. A.; Kallepalli, V. A.; Maleczka, R. E., Jr; Smith, M. R., III (Tetrahedron, 2008)

(untitled) - Palamà, I.; Di Maria, F.; Viola, I.; Fabiano, E.; Gigli, G.; Bettini, C.; Barbarella, G. (J. Am. Chem. Soc., 2011)

(untitled) - Klingstedt, T.; Shirani, H.; Mahler, J.; Wegenast-Braun, B. M.; Nyström, S.; Goedert, M.; Jucker, M.; Nilsson, K. P. R. (Chem. – Eur. J., 2015)

(untitled) - Simon, R. A.; Shirani, H.; Åslund, K. O. A.; Bäck, M.; Haroutunian, V.; Gandy, S.; Nilsson, K. P. R. (Chem. – Eur. J., 2014)

(untitled) - Roubinet, B.; Bossi, M. L.; Alt, P.; Leutenegger, M.; Shojaei, H.; Schnorrenberg, S.; Nizamov, S.; Irie, M.; Belov, V. N.; Hell, S. W. (Angew. Chem., Int. Ed., 2016)
Angew. Chem., 2016, 128, 15655–15659. doi:10.1002/ange.201607940

(untitled) - Yamaguchi, T.; Irie, M. (J. Photochem. Photobiol., A, 2006)

(untitled) - Henriques, R.; Griffiths, C.; Hesper Rego, E.; Mhlanga, M. M. (Biopolymers, 2011)

(untitled) - Balzarotti, F.; Eilers, Y.; Gwosch, K. C.; Gynnå, A. H.; Westphal, V.; Stefani, F. D.; Elf, J.; Hell, S. W. (Science, 2017)

(untitled) - Kashihara, R.; Morimoto, M.; Ito, S.; Miyasaka, H.; Irie, M. (J. Am. Chem. Soc., 2017)

(untitled) - Arai, Y.; Ito, S.; Fujita, H.; Yoneda, Y.; Kaji, T.; Takei, S.; Kashihara, R.; Morimoto, M.; Irie, M.; Miyasaka, H. (Chem. Commun., 2017)

(untitled) - Uno, K.; Bossi, M. L.; Irie, M.; Belov, V. N.; Hell, S. W. (J. Am. Chem. Soc., 2019)